Comparative growth and survival of hatchery-produced oyster seeds' between two culture sites located in West and East Malaysia. - Yasin, Zulfigar (Universiti Sains Malaysia, 2002)

(untitled)
Oysters have been consumed traditionally in Malaysia.The small oysters harvested from the wild stocks served as omelets are favourite local food, especially among the chines community.The production from wild sources was estimated approximately 150 MT per year by the Bay of Bengal Programme of the FAO.Oysters are perceived to be on expensive food and not an everyday dish by most consumers.